Gender-based Analysis of Interactional Markers in Personal Essays - Sasmita Ratna Puspita; Suhandano (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study examined the interactional metadiscourse devices and the correlation with gender in personal essays. The data was taken from 20 essays, 10 essays from each respective genders which are published by Chicken Soup for the Soul in several editions. Tokens of interactional metadiscourse devices were obtained by using corpus software Antconc 3.5.9. The occurrence then underwent qualitative examination to sort only items used as interactional devices based on interactional metadiscourse taxonomy proposed by Hyland. This feature have been widely used to identify the interaction and meaning-making in many persuasive and academic writings as well as talks such as TED talks. To fill the gap, this study aimed to see the differences of interactional metadiscourse devices usage by women and men in personal essays. The result shows that women use more interactional discourse markers than men except for hedges category. In general, women use more interactional discourse in personal essays to express themselves and to let their readers feel being engaged in the story through emotive connections. Whereas, men write their stories more directly and attract the reader on the sequence of events.